Averaged power spectrum density, fractal and multifractal spectra of Au nano-particles deposited onto annealed TiO2 thin films - Solaymani, Shahram; Yadav, Ram Pratap; Ţălu, Ştefan; Achour, Amine; Rezaee, Sahar; Nezafat, Negin Beryani (Optical and quantum electronics, 2020)
This work describes the morphology of titanium oxide (TiO 2 ) thin films deposited by gold nanoparticles and produced at room temperature over Si(100) wafers. A direct-current (DC) reactive magnetron sputtering process was applied for the sample preparation. Then, their three-dimensional (3-D) surface characterization was carried out by using atomic force microscopy (AFM). Stereometric analysis was carrying out on the basis of AFM-data, and the surface topography was described according to ISO 25,178–2:2012 standard. As can be seen, the surface of sample #3 has the most regular topography (Df = 2.70 ± 0.01) with the most regular surface (Sq = 0.97 nm). The most irregular topography (Df = 2.83 ± 0.01) was found in sample #2, while the most irregular surface (Sq = 3.38 nm) was found in sample #1.